After antiquity: Joseph and Aseneth in manuscript transmission. A case study for engaging with what came after the original version of Jewish Pseudepigrapha. - Wright, J (2018)
The story of Joseph and Aseneth expands a few verses from the book of Genesis into a novella- length work. In recent years, the story has attracted considerable scholarly attention. Interest has focused on questions of provenance: whether the 'longer' or 'shorter' version of the text has prior- ity, and what this means for its interpretation. Like other works of the so-called 'Jewish Pseud- epigrapha', it is increasingly used as a source for Judaism and Christianity at the turn of the Com- mon Era. But few have engaged with the story's manuscript witness and transmission. This thesis returns to the sources. It considers how the redaction and translation of Joseph and Aseneth affected its interpretation, and looks at the interests of the redactors and copyists. It warns against placing too much weight on details that lack such an importance in the manuscript tradition. The introduction surveys modern secondary literature on the story. Section 1 investigates the translation and transmission context of the two earliest preserved versions, the Syriac and Armeni- an translations. Despite their text-critical importance, they have received little attention. Section 2 focuses on the Greek manuscripts of the three longest families (f, Mc, a). It argues that these re- dactions, and the variety within their witnesses, need to be understood within a Byzantine context, in particular, within hagiographic trends for works produced in monastic environment. Section 3 looks at how the story could be abridged and edited. It identifies the key elements of the story shared by redactors. Four versions are compared: family d, E, Latin 1 and so-called "early modern Greek". The appendices contain a synoptic presentation of Greek versions of the story, an edition and translation of the story from manuscript E, and a translation of the Greek text from manu- script 661.